The Free-Ranging Italian Wolf (Canis lupus italicus): A Study of the Circulation of DNA and RNA Viruses in Three Italian Regions - Musto, Carmela (Alma Mater Studiorum - Università di Bologna, 2020)
This dataset is part of my Ph.D. research, which assesses the presence and the spread of DNA and RNA viruses in the free-ranging wolves found dead in Emilia-Romagna, Tuscany, and Calabria from August 2017 to July 2020. The research investigated through molecular methods the genomic DNA presence of three important DNA viruses (CPV-2 Canine Parvovirus type-2, CAdV-1 Canine Adenovirus type-1, CAdV-2 Canine Adenovirus type-2). Furthermore, the presence of genomic RNA of the important RNA viruses, Canine Coronavirus (CCoV) and Canine Distemper Virus (CDV), was also investigated. This dataset information will contribute to improve the knowledge of dog-wolf interface infectious diseases.